The Role of Conversation in Family Communication for Gay Homosexual Individuals. - Nurrezqia, Agnessya; Rina, Nofha (Indonesian Journal of Social Science Research, 2024)
This research discusses the role of family communication in the formation of gay identity through conversational orientation. Early education on the classification of sexual roles provided by parents is expected to serve as a reference for individual behavior. Through family communication, a social construction is built by the family that evolves with their experiences and meanings as they face challenges and difficulties. This study uses a qualitative method with a phenomenological approach and snowball sampling to collect data from gay individuals. Data analysis was conducted using thematic analysis aided by qualitative software Atlas.ti V.9. The results show that conversational orientation within the family plays a significant role in shaping the identity and behavior of gay individuals. The main findings include six conversational themes: openness in expressing opinions and discussing issues, parental expectations of children's behavior, positive messages and motivation, passive parental roles, reserved communication, and verbal abuse. Open communication within the family helps gay individuals feel accepted and supported, while closed or negative communication tends to lead to isolation and decreased self-confidence. This research emphasizes the importance of open and inclusive family communication in addressing issues of sexuality.